Prevalence, burden of disease, and lost in health state utilities attributable to chronic musculoskeletal disorders and pain in Chile - Pedro Zitko; Norberto Bilbeny; Carlos Balmaceda; Tomas Abbott; Cesar Carcamo; Manuel Espinoza (BMC, 2021)
Abstract Background Musculoskeletal disorders are a leading cause of disability adjusted life years (DALY) in the world. We aim to describe the prevalence and to compare the DALYs and loss of health state utilities (LHSU) attributable to common musculoskeletal disorders in Chile. Methods We used data from the Chilean National Health Survey carried out in 2016-2017. Six musculoskeletal disorders were detected through the COPCOPRD questionnaire: chronic musculoskeletal pain, chronic low back pain, chronic shoulder pain, osteoarthritis of hip and knee, and fibromyalgia. We calculated the DALY for each disorder for 18 sex and age strata, and LHSU following an individual and population level approaches. We also calculated the fraction of LHSU attributable to pain. Results Chronic musculoskeletal pain disorder affects a fifth of the adult population, with a significant difference between sexes. Among specific musculoskeletal disorders highlights chronic low back pain with the highest prevalence. Musculoskeletal disorders are a significant cause of LHSU at the individual level, especially in the case of fibromyalgia. Chronic musculoskeletal pain caused 503,919 [283,940 - 815,132] DALYs in 2017, and roughly two hundred thousand LSHU at population level, which represents 9.7% [8.8-10.6] of the total LSHU occurred in that year. Discrepancy in the burden of musculoskeletal disorders was observed according to DALY or LSHU estimation. The pain and discomfort domain of LHSU accounted for around half of total LHSU in people with musculoskeletal disorders. Conclusion Chronic musculoskeletal pain is a major source of burden and LHSU. Fibromyalgia should deserve more attention in future studies. Using the attributable fraction offers a straightforward and flexible way to explore the burden of musculoskeletal disorders.